CASE REPORT OF A PATIENT WITH INAFFECTIVE BREATHING PATTERN IN COPD IN THE MARWAH AND RAUDHAH ROOMS OF PKU MUHAMMADIYAH HOSPITAL YOGYAKARTA - Allama Zaki Almubarok; Muhammad G.A. Putra (JTH: Journal of Technology and Health, 2024)
Chronic Obstructive Pulmonary Disease is a term often used for a group of lung diseases that last a long time and are characterized by increased resistance to air flow as the main pathophysiological feature. The third disease that forms a single unit known as COPD (Chronic Obstructive Pulmonary Disease) is bronchial asthma, chronic bronchitis and pulmonary emphysema. Objective: Able to provide and apply nursing care to COPD patients with a diagnosis of ineffective breathing patterns in the Raudhah room and Marwah room of PKU Muhammadiyyah Yogyakarta. This research method is observational case study research with a cross sectional approach design. The research subjects in this case study were 2 patients at PKU Muhammadiyah Yogyakarta with respiratory system disorders with a medical diagnosis of COPD. Results: From the results of the assessment and physical examination, data was obtained that the two patients were coughing, short of breath, appeared weak, appeared to be pulling in the chest wall, used accessory muscles for breathing, had additional breath sounds, and were breathing rapidly. The primary diagnosis of swelling is ineffective breathing pattern related to hyperventilation. The expected achievement in both cases with a diagnosis of ineffective breathing patterns related to hyperventilation is no difference, namely within 3 days of intervention in the first case and in the second case the treatment problem was partially resolved. Suggestion: It is hoped that for nurses, this scientific paper can be applied in carrying out nursing care for adult patients with COPD so that they can improve mutual care services.